(3GdeUHGM GdoeVF aj cJGH GdfHj GdCej hQSdg Edi edhc GdCQV ef YLej hYQHjs - (3CHh YHO Gddg eMeO Hf Ydj Hf CMeO Hf MOjOI GdCfUGQj GdNRQLj GdebOSj GdeUQj, GHf MOjOI,J (B783 (3g` s ((3YKeGf GdOjQHj s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdOjGf , Pj GdYRI hGdSdWGf s
(3LYdg Ydi bSejf(B: (3GdChd ai cJGHg hGdKGfj ai QSdg hecGJHI Gdedhc haQZ ef JCdjag HeUQ ai Pj GdbYOI SfI(B779(3g`s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B286s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B72 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B144 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1710s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs